Prison health situation and health rights of young people incarcerated in sub-Saharan African prisons and detention centres: a scoping review of extant literature - Marie-Claire Van Hout; Rosemary Mhlanga-Gunda (BMC, 2019)
Abstract Background Treatment and special protection of the rights of incarcerated young people in prisons are mandated under the Sustainable Development Goals (SDG), as well as under United Nations (UN) human rights instruments. Methods A scoping review mapped what is currently known about prison conditions and health situation of detained and incarcerated young people in sub- Saharan African (SSA) prisons. A systematic search collected and reviewed all available and relevant published and grey literature. Following application of exclusion measures, 54 records remained, which represented 37 of the 49 SSA countries. These records were charted and thematically analysed. Results The ages of children and adolescents held in SSA prisons ranged from 12 to 18 years. Three main themes were generated during the charting exercise; the prison environment for young people; availability and accessibility of basic necessities and navigating the prison system for health care and outside continuum of care. Conclusions The review highlights the grave and continuing deplorable situation of young people held in SSA prisons. The violation of international human rights norms is observed in the systemic abuse and detention of young people with adults. Basic needs are not met in relation to sanitation, ventilation, safe spaces, protection from physical and sexual violence, clothing, food and access to HIV and medical care.